2004
DOI: 10.1111/j.1365-2516.2004.00924.x
|View full text |Cite
|
Sign up to set email alerts
|

Unresponsiveness to factor VIII inhibitor bypassing agents during haemostatic treatment for life‐threatening massive bleeding in a patient with haemophilia A and a high responding inhibitor

Abstract: We report a case of haemophilia A with a high responding inhibitor of factor VIII (FVIII) who had a serious retroperitoneal haematoma caused by penetration of a duodenal ulcer. Inhibitor-bypassing therapy was commenced immediately on admission. On the 17th day of treatment with activated prothrombin complex concentrate (APCC; FEIBA, re-bleeding occurred and thrombelastography (TEG) demonstrated resistance to therapy. Treatment was changed to recombinant activated factor VII (rFVIIa; NovoSeven and resulted in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
53
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 11 publications
0
53
0
1
Order By: Relevance
“…Although both tests have been proposed to be useful for rFVIIa monitoring in hemophilia patients [12][13][14], prospective clinical trials linking a specific laboratory parameter to the rFVIIa clinical response are lacking. With regard to the clinical effect of rFVIIa no such correlation exists although there are a few anecdotal case reports [3,15]. Both thromboelastography [16] and the thrombin generation tests are subject to great variability, and the lack of standardized assay conditions makes comparison between laboratories difficult.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Although both tests have been proposed to be useful for rFVIIa monitoring in hemophilia patients [12][13][14], prospective clinical trials linking a specific laboratory parameter to the rFVIIa clinical response are lacking. With regard to the clinical effect of rFVIIa no such correlation exists although there are a few anecdotal case reports [3,15]. Both thromboelastography [16] and the thrombin generation tests are subject to great variability, and the lack of standardized assay conditions makes comparison between laboratories difficult.…”
Section: Introductionmentioning
confidence: 95%
“…Clinical experience however has shown that there can be a wide variation in the hemostatic response, and in some cases a low response to rFVIIa has been observed [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Поэтому ТЭГ в настоящее время является од-ним из наиболее принятых методов мониторинга те-рапии rFVIIa у пациентов с ингибиторной формой гемофилии [9,13,14]. Использование ТЭГ позволяет не только мониторировать терапию шунтирующими препаратами, но и выявлять резистентность к одно-му из них, вовремя изменить тактику гемостатиче-ской терапии, индивидуализировать лечение [6,15]. Наиболее информативной для этого является оценка таких параметров ТЭГ, как период R и интервал МА, они позволяют даже дифференцировать больных ге-мофилией с тяжелой формой, умеренной тяжести и легкого течения [5].…”
Section: Discussionunclassified
“…Thus, as an alternative to APCC therapy, successful control of hemostasis by rFVIIa was documented in patients with inhibitors [16]. The short half-life of rFVIIa (3.5 hr) [17], however, makes it difficult to optimize the interval of regular infusion for prophylaxis. Sequential administration of APCC and rFVIIa has been effectively used on occasion.…”
Section: Discussionmentioning
confidence: 99%
“…Sequential administration of APCC and rFVIIa has been effectively used on occasion. Hayashi et al [17] and Schneiderman et al [18] reported that a regimen that alternated between APCC and rFVIIa was effective for treatment of inhibitor-positive patients with refractory bleeding that was not effectively controlled with either agent alone. However, the sequential use of PCCs/APCCs and FVIIa may be problematic, as illustrated by the development of thrombotic events, one of which was fatal, in two patients receiving PCCs and rVIIa [19].…”
Section: Discussionmentioning
confidence: 99%